Strain effects on the macroscopic behaviour and martensite morphology in shape-memory CuZnAl alloys - Kayali, N; Özgen, S; Adigüzel, O (Elsevier Science Sa, 2000)
Shape-memory alloys exhibit super-elasticity when they are deformed at a temperature less than the transformation temperature. The specimen remains in the deformed shape on releasing the strain at this temperature but recovers the undeformed original shape on heating to temperatures over the reverse transformation temperature. As a result of their ability to generate spontaneous shape changes on thermal cycling, these alloys can convert heat directly into mechanical work due to the substantial recovery stresses generated during the martensite-to-parent transformation. These alloys are very sensitive to thermal effects and are influenced strongly by both quenching and post-quench heat-treatments. The effects of external stress on the character of the macroscopic shape in two shape-memory CuZnAl alloys are investigated. The effects of post-quench heat-treatment on martensite morphology were observed by means of optical microscopy. Thermal hysteresis occurring during the heating and cooling processes is attributed to internal friction. Furthermore, parallel-sided martensite plates which can be grown almost in one dimension have been observed in the post-quench hear-treated specimens. It is suggested that the equilibrium phase (alpha-fcc) formed in the aged specimens causes the loss of shape memory. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: martensitic transformation; shape-memory alloy; elongation parameter; martensite morphology; subgrain